Enhancing culture sensitive social work practice: religious and ethical aspects of the new reproductive technologies (NR Ts) - Sewpaul, V (Social Work/Maatskaplike Werk, 2001)
Social workers are being increasingly called upon, especially within interdisciplinary teams, to participate in complex ethical decision making that requires cultural sensitivity and cultural competence. The development of cultural sensitivity, cultural competence and respect for religious and cultural diversity is enhanced by increasing our knowledge of clients' frames of reference. llrrough the use of a qualitative, interpretative, feminist research methodology that guided an empiiical approach to data collection via twenty-four case studies, this study explored the relationship between religious and ethical beliefs and new reproductive technologies (NR Ts) Sewpaul, 1995). Given the particular focus of the study, efforts were made to ensure that cultural and religious diversity were represented in the sample. While race is not equivalent to culture, in the South African context a person's cultural beliefs (especially religious affiliation and religious beliefs) are more often than not linked to the ethnic group from which they come. Thus efforts were made to ensure inclusion of African, Indian, Coloured and White1 participants in the study. All seven of the Indian couples belonged to the Hindu faith. All others in the sample were of the Christian faith, with all of the African couples subscribing to both Christianity and African Traditional Religion. All the African couples indicated that, while they held their Christian faith to be important, it was African Traditional Religion that they turned to when dealing with significant aspects of their lives. Thus, as far as religion was concerned, the African couples appeared to be successfully biculturally socialised. While they were affiliated to Western religion, they were at the same time quite profoundly connected with African Traditional Religion (Sewpaul, 1999).